Pengaruh Model Pembelajaran Langsung Berbasis Praktikum terhadap Sikap Ilmiah Siswa Kelas VII SMP Negeri 1 Gangga - Pariani, Pariani (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
The purpose of this research is to determine the effect of a direct, practicum-based learning model on the scientific attitudes of class VII students at SMP Negeri 1 Gangga, North Lombok Regency. This research is a quasi-experimental research with a Pretest Posttest Control Group Design. The population in this study were all class VII students at SMP Negeri 1 Gangga, with the research sample consisting of two classes, namely class VII A with 28 students as the experimental class and class VII B with 28 students as the control class taken using random sampling techniques. Based on the research results, it is known that both classes experienced an increase in scientific attitudes. The percentage of scientific attitudes of the experimental class and control class was 74.51% and 67.65% respectively, increasing to 86.27% and 72.55%. The results of this research indicate that there is an influence of the practical-based direct learning model on the scientific attitudes of class VII students at SMP Negeri 1 Gangga.